PERBANDINGAN PERFORMA METODE INTERPOLASI POLINOMIAL NEWTON-GREGORY MAJU DAN NEWTON-GREGORY MUNDUR DALAM MENGESTIMASI JUMLAH PENDUDUK DI PROVINSI PAPUA - Agus Firanto; Darsih Idayani (Jurnal Matematika Sains dan Teknologi, 2022)
Population data is one of the absolute requirements that must be fulfilled by the Central Statistics Agency (Badan Pusat Statistik) to determine the grand design of development in the Province of Papua. However, the most complete and accurate source of population data comes from the results of a population census carried out every ten years. With long intervals and requiring costs, time, and effort, it will be more efficient and save time and effort if the number of residents can be estimated. Estimating the population required the proper method. Therefore, in this article, a comparison of Forward Newton-Gregory Polynomial Interpolation and Backward Newton-Gregory Polynomial Interpolation techniques is carried out to estimate the population of Papua Province. The estimated results of the two methods are compared by comparing the relative amount of error. The comparison results show that the relative error average of the Forward Newton-Gregory Polynomial Interpolation 0,014200679 is smaller than the relative error average of the Backward Newton-Gregory Polynomial Interpolation 0,047163677. So, it can be concluded that the Forward Newton-Gregory Polynomial Interpolation method is better than Backwards Newton-Gregory Polynomial Interpolation in predicting the population of Papua Province.